The essence, methods and results of assessing profitability of a non-public university - Trippner, Paweł; Jóźwicki, Rafał (Journal of Finance and Financial Law, 2022)
The aim of the study is to present the meaning, structure and principles of financing higher education in Poland. The division into public and non-public higher education is presented and the authors focused on the sources of financing non-public higher education, which does not benefit from budget subsidies. The most important sources of financing activities of non-public higher education were indicated. Another objective of the paper is to characterize the role, essence and importance of the financial controlling department in the management of economic entities including non-public higher education institutions. The authors’ interests is also focused on financial documents, which provide data to evaluate the financial situation of an economic entity as well as financial measures used during the analysis. Finally, an assessment of the level of profitability of a non-public higher education institution is made with a detailed division into full-time, extramural and postgraduate studies. The revenue structure of the studied entity was also compared to the market of non-public higher education institutions in Poland. The essence of functioning of the financial controlling department in a company and the tasks and role of a financial controller are additionally presented in the paper. The methodology used in the submitted article is a financial analysis of non-public university’s financial statement based on profitability ratios. The article deals with the occasional subject of evaluation of non-public university functioning by the Financial Controlling Department in terms of income generated, costs incurred and profitability level achieved. The functioning of higher education in Poland should be divided into two areas: state universities, which benefit from budget subsidies for students studying on a full-time basis, and non-public higher education institutions, which may or may not benefit from such subsidies. Their primary source of income is fees paid by students in various forms, mainly in the form of tuition fees. Non-public sector of higher education in Poland doesn’t use public budget grants so the importance of Financial Controlling Departments is essential in calculating incomes and costs. The data used in the analyses came from a private institution in the higher education sector. The owner of the company did not agree to provide its name and the detailed figures based on which the financial ratios were calculated.